Augmented EFIE with Adaptive Cross Approximation Algorithm for Analysis of Electromagnetic Problems - D. Z. Ding; Y. Shi; Z. N. Jiang; R. S. Chen (International Journal of Antennas and Propagation)
The augmented electric field integral equation (A-EFIE) with charge neutrality enforcement provides a stable formulation to conquer low-frequency breakdown characteristic of conventional EFIE. It is augmented with additional charge unknowns through current continuity equation. The A-EFIE combined with the multilevel adaptive cross-approximation (MLACA) algorithm is developed to further reduce the memory requirement and computation time for analyzing electromagnetic problems. Numerical examples are given to demonstrate the accuracy and efficiency of the proposed method.